(untitled) (Journal of International Studies, 2016)
The objective of this study is to explore the application of trade-related environmental measures in Malaysia. Trade-related environmental measures are environmental measures that were invoked which may have an effect on international trade. These measures can be in the form of tariff and non- tariff. As a member of the World Trade Organization (WTO), Malaysia is compelled to apply and implement the environmental provisions of the General Agreement of Tariff and Trade (GATT) and the WTO agreements. However, the ability to fully comply with these agreements needs to be determined as Malaysia’s effort in environmental protection could affect its international trading. In this study the analysis was on Malaysia’s domestic legislations; the GATT, especially Article XX; WTO agreements such as the Agreement on the Application of Sanitary and Phytosanitary Measures (SPS), the Agreement on Technical Barriers to Trade (TBT) and the WTO Dispute Settlement Body decided cases. Secondary data such as journal articles were referred. It is expected that this study could assist in determining the efforts made by Malaysia in finding a balance between international trade and environmental protection.